ANALISIS LABA DAN ARUS KAS OPERASI SEBAGAI PREDIKTOR ARUS KAS DI MASA DEPAN - Budiyasa, A.A. Putu Merta; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
This study aims to provide empirical evidence about the effect of gross profit, operating income, net income and operating cash flow as predictor of the future cash flow. The study was conducted on companies listedson the Indonesia Stock Exchange. The sample is determined by purposive sampling method of 51 companies with 134 observations. Data obtained from www.idx.co.id. Data were analyzed using multiple regression analysis techniques. Results of thish study conclude that gross income, operating income, and operating cash flow take effect on operating cash flow in the future, only net income variable do not affect the operating cash  flow  in  the  future. It is suggested that further research might  use a longer study period and additional variables to obtain a better predictor.
Keywords: Gross income, Operating Income, Net Income, Operating Cash Flow, Operating Cash Flow Prediction